Pregnancy outcomes after fresh versus vitrified-warmed embryo transfer in women with adenomyosis: a retrospective cohort study. Issue 6 (June 2022) - Zhu, Xingwang; Dongye, Houjin; Lu, Shaoming; Zhao, Xingbo; Yan, Lei
Abstract: Research question: Is the singleton live birth rate superior for vitrified-warmed versus fresh embryo transfer in women with adenomyosis? Design: This cohort study retrospectively analysed data from the Reproductive Hospital Affiliated to Shandong University between January 2013 and December 2018. A total of 612 women diagnosed with adenomyosis, with 322 fresh embryo transfer cycles and 290 vitrified-warmed embryo transfer cycles, were included in this study. The primary outcome was singleton live birth. Outcomes were adjusted using multivariable logistic regression analysis. Results: Vitrified-warmed embryo transfer was associated with a higher rate of singleton live birth than fresh embryo transfer (25.9% versus 17.4%; P  = 0.011). Although there was a trend towards a lower miscarriage rate after vitrified-warmed embryo transfer, the difference did not reach statistical significance (31.3% versus 40.6%; P  = 0.111). The clinical pregnancy rate was comparable in the two groups (44.1% versus 44.4%; P  = 0.946). Vitrified-warmed embryo transfer also resulted in a lower risk of preterm birth than fresh embryo transfer (7.0% versus 17.5%; P  = 0.010). Conclusions: Vitrified-warmed embryo transfer may be associated with better pregnancy outcomes than fresh embryo transfer among women with adenomyosis. It seems that vitrified-warmed embryo transfer is more appropriate for specific populations.